A new pyranoxanthone from Garcinia nervosa. Issue 21 (2nd November 2017) - Wong, Ka Woong; Ee, Gwendoline Cheng Lian; Ismail, Intan Safinar; Karunakaran, Thiruventhan; Jong, Vivien Yi Mian
Abstract: Phytochemical studies on the stem bark of Garcinia nervosa has resulted in the discovery of one new pyranoxanthone derivative, garner xanthone (1 ) and five other compounds, 1, 5-dihydroxyxanthone (2 ), 6-deoxyisojacareubin (3 ), 12b-hydroxy-des-D-garcigerrin A (4 ) stigmasterol (5 ), and β -sitosterol (6 ). The structures of these compounds were elucidated with the aid of spectroscopic techniques, such as NMR and MS. The crude extracts of the plant were assessed for their antimicrobial activity. Abstract :